Faith-Based Water Sanitation and Hygiene Initiatives: Effects on Pastoral Livelihood in Marsabit County, Kenya - Beatrice Kirujah; Petronilla Otuya; Duncan Ochieng (Adventist University of Africa, 2023)
Background: In Marsabit County, pastoralists face challenges such as scarce clean water, proper hygiene, inadequate sanitation, and limited socioeconomic well-being. This study assessed the effects of Water, Sanitation, and Hygiene (WASH) initiatives by faith-based organizations (FBOs) on pastoral livelihoods in Marsabit County. The study was guided by three objectives: To assess the extent to which faith-based organizations' water sanitation and hygiene initiatives enhanced access to adequate safe and clean water among pastoral communities in Saku, Sub County, Marsabit County, Kenya, to evaluate the extent to which faith-based organizations' water sanitation and hygiene initiatives enhanced changes in sanitation facilities and hygiene practices among pastoral communities in Saku Sub County, Marsabit County, Kenya and to examine the extent to which faith-based organizations' water sanitation and hygiene initiatives enhanced food security and income generation among pastoralists in Saku Sub County, Marsabit County, Kenya. Method: Using a stratified sampling technique, the study's target population comprised 2004 individuals and a representative sample of 323 household heads. Structured questionnaires were used to collect data from household heads. Thematic analysis was applied to explain the questionnaire responses further, incorporating qualitative data gathered from two Key Informant Interviews and two Focus Group Discussions. Results: The main findings revealed enhanced access to safe and clean water, hygienic sanitation, food, and improved income for the targeted community. Conclusion: This study confirmed that WASH initiatives enhanced the livelihoods of the target population. To further reinforce pastoral livelihoods, concerted interventions by the government is necessary for larger infrastructure.